How should we teach the logic of BPM? Comparing e-learning and face-to-face setting in situated learning - Leyer, Michael; Wang, Minhong; Moormann, Juergen (ACIS, 2014)
Knowing the fundamental idea of Business Process Management (BPM) is essential for students to understand and connect concepts of BPM and to develop appropriate information systems (IS). The idea of BPM refers to the logic how organizations and processes should be designed to be efficient independent from the context. But the question arises how to enable students to learn the idea of BPM. We conducted an empirical study with 150 graduate students separated into e-learning and face-to-face groups. The results show that both learning settings are effective, but the effect of the face-to-face setting is almost twice as high as in the e-learning setting. We propose to use situated e-learning as a short introduction for beginner courses in IS. Thus, students can quickly accumulate a sufficient level of knowledge. A situated face-to-face setting is then helpful to deepen the knowledge in a course on specific concepts of BPM.